2013
DOI: 10.4103/2141-9248.117944
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence and attitudes regarding its control among health professional students in South-Western Nigeria

Abstract: Background:Tobacco use is one of the leading preventable causes of morbidity and mortality globally; about 70% of smokers see physicians each year. Health care professionals have a very unique role in motivating people to quit smoking.Aim:The aims of this study were to document the smoking prevalence and attitudes regarding its control among these set of students who will be tomorrow's health care providers.Subjects and Methods:A cross-sectional survey was conducted in two medical schools in South-Western Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
9
12
0
Order By: Relevance
“…Smoking prevalence was higher among males than females similar to other studies that showed that the frequency of tobacco use differs significantly between sexes 11,19 . A higher acceptability and use among males is suggested 20 .…”
Section: Smoking Prevalence and Patternssupporting
confidence: 76%
See 4 more Smart Citations
“…Smoking prevalence was higher among males than females similar to other studies that showed that the frequency of tobacco use differs significantly between sexes 11,19 . A higher acceptability and use among males is suggested 20 .…”
Section: Smoking Prevalence and Patternssupporting
confidence: 76%
“…Also, most respondents opined that both pharmacy students and pharmacists in general should be involved in smoking cessation programmes.These findings mimic a recent study 11 .As a matter of fact, it is reported that about 5-10% abstinence rates may be achieved following counseling by a health pratitioner 36 It is gratifying to note that, these students had a very positive attitude towards smoking and smoking cessation with a mean perception of 4.05 (81%). If this attitude is maintained and sustained, then we may be hopeful that, in the near future, there will be more people involved in the struggle to curtail the smoking pandemic.…”
Section: Pharmacists Pharmacies and Smokingsupporting
confidence: 69%
See 3 more Smart Citations